2021
DOI: 10.1016/j.jqsrt.2021.107510
|View full text |Cite
|
Sign up to set email alerts
|

Toward measurements of the speed-dependence of line-mixing

Abstract: We theoretically demonstrate that some doublets of NH 3 broadened by Ar and heavier atoms may be suitable for the first experimental demonstration of a so-far unstudied problem: The spectral effects of the speed dependence of line-mixing. By using realistic assumptions and spectroscopic data from previous studies, we show that neglecting this process leads to errors on the spectral shape of up to 2% of the peak absorption value. When multispectrum fits are made assuming speed-independent line couplings, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…The latter was evaluated and found to be negligible under our experimental conditions in accordance with conclusions of work Ref. [69]. The use of the speed dependent parameter Y (v) instead of the speed averaged value Y in calculations of the line shape (Eq.…”
Section: Line-shape Parameterssupporting
confidence: 83%
“…The latter was evaluated and found to be negligible under our experimental conditions in accordance with conclusions of work Ref. [69]. The use of the speed dependent parameter Y (v) instead of the speed averaged value Y in calculations of the line shape (Eq.…”
Section: Line-shape Parameterssupporting
confidence: 83%
“…The perturbation of the spectra of ammonia in argon baths has lead to numerous studies [1][2][3][4][5][6][7][8][9][10][11]. Most of these studies dealt with the pressure broadening and shift coefficients but some also addressed the line mixing effect.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge the speed dependence of the pressure broadening and shift has received little attention for this system [3,6,12] and the speed dependence of the line mixing completely disregarded. Recently, on the basis of the quadratic [13] or hypergeometric [14] models often used to model the speed dependence of the collisional broadening, Boulet et al [11] have suggested that the speed dependence of intradoublet coupling coefficients could be observed in the ν 4 band of ammonia in argon. In order to check this proposition we have performed dynamical calculations on a potential energy surface (PES) [15].…”
Section: Introductionmentioning
confidence: 99%